Hubungan Kinerja Perawat Profesional dengan Praktik Klinik Keperawatan Medikal Bedah Mahasiswa Profesi Ners di RSUD Jayapura Profinsi Papua - John Toding Padang; Novita Medyati (STIKes Patria Husada Blitar, 2014)
Clinical practice experience is a kind of learning that must be done in nursing education. Result of job performance of an organization needs measurement standard so the assessment of performance is an essential aspect for hospitals to improve nurse professional performance. Students attendance at nursing clinical practice creates function, role and responsibility in supervisory activities of heads of wards, nurses, and clinical supervisors. Purpose of this study was to assess nurse performance at Jayapura Hospital, Province of Papua in the implementation of medical surgical nursing clinical practice of nursing profession students. Method: Research study was descriptive with cross sectional design. Research sample was73 consist of 7 heads nurse, 58 nurses, and 8 clinical instructor at inpatient rooms and 49 nursing profession students. Data collected at July 2nd until 16th, 2014 by using self-administered questionaire and proceeded using software. The conclusion is availability of the study average performance of nurses was high. However according to students evaluation average performance of nurses was adequate